Type-II WS2–ReSe2 heterostructure and its charge-transfer properties. Issue 11 (15th June 2020) - Han, Xiuxiu; He, Dawei; Zhang, Lu; Hao, Shengcai; Liu, Shuangyan; Fu, Jialu; Miao, Qing; He, Jiaqi; Wang, Yongsheng; Zhao, Hui
Abstract: Abstract : We fabricated a van der Waals heterostructure of WS2 –ReSe2 and studied its charge-transfer properties. Monolayers of WS2 and ReSe2 were obtained by mechanical exfoliation and chemical vapor deposition, respectively. The heterostructure sample was fabricated by transferring the WS2 monolayer on top of ReSe2 by a dry transfer process. Photoluminescence quenching was observed in the heterostructure, indicating efficient interlayer charge transfer. Transient absorption measurements show that holes can efficiently transfer from WS2 to ReSe2 on an ultrafast timescale. Meanwhile, electron transfer from ReSe2 to WS2 was also observed. The charge-transfer properties show that monolayers of ReSe2 and WS2 form a type-II band alignment, instead of type-I as predicted by theory. The type-II alignment is further confirmed by the observation of extended photocarrier lifetimes in the heterostructure. These results provide useful information for developing van der Waals heterostructure involving ReSe2 for novel electronic and optoelectronic applications and introduce ReSe2 to the family of two-dimensional materials to construct van der Waals heterostructures.